Manajemen Nyeri Asuhan Keperawatan Pasien Pasca Operasi Pada Tn.D Dan Ny.N Dengan Urolithiasis Post Op Percutaneous Nephrolithotomy (PNCL) Di Rumah Sakit Wilayah Jakarta - Gusrina Komara Putri (Indonesian Journal of Nursing Scientific, 2023)
Background: Urolithiasis is one of the diseases of the urinary system that ranks third in the field of urology. Purpose: This case study aims to describe and be able to provide nursing care to patients with urolithiasis after PNCL surgery. Methods: The research design used is descriptive analytic with a case study approach in nursing care, literature study, and data collection with the number of samples being two patients, namely Mr. D and Mrs. N. Results: After nursing care for 3x24 hours, the results of Mr. D has decreased from a pain scale of six to three. Conclusion: Nursing care that has been implemented is pain management is effectively carried out. In this case nurses play an important role in conducting comprehensive assessments, establishing diagnoses, making nursing interventions, collaborating with other health workers in providing nursing care to patients, evaluating and following up, so as to improve the quality of life of patients.